2006
DOI: 10.1157/13093369
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de los estudios publicados sobre el incumplimiento terapéutico en el tratamiento de la hipertensión arterial en España entre los años 1984 y 2005

Abstract: The percentage of therapy non-compliance in the treatment of hypertension in Spain has fallen in recent years, although it continues to be high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…This lack of knowledge is also consistent with other studies carried out in Spain, in which they revealed that over 50% of Spanish patients with hypertension did not follow adequately their physicians’ recommendations (Márquez Contreras et al . ). This might have account for why 65% of Spanish patients on antihypertensive drug regimens did not have their blood pressure under adequate control (Banegas ).…”
Section: Discussionmentioning
confidence: 97%
“…This lack of knowledge is also consistent with other studies carried out in Spain, in which they revealed that over 50% of Spanish patients with hypertension did not follow adequately their physicians’ recommendations (Márquez Contreras et al . ). This might have account for why 65% of Spanish patients on antihypertensive drug regimens did not have their blood pressure under adequate control (Banegas ).…”
Section: Discussionmentioning
confidence: 97%
“…Márquez Contreras et al 11 warned that questionnaires have low negative predictive value, confi rmed by the fact that 43% of users with uncontrolled high blood pressure reported that they were correctly following their treatment. Another important factor is reported by Santa Helena et al, 16 and refers to the conditions in which the questionnaire is carried out, dealing with undesirable behavior, which may intimidate the interviewees.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strategies that have most improved compliance among subjects with other risk factors, such as hypertension, do not include specific activities, such as pamphlets or telephone alerts, but rather combined activities, such as group sessions coupled with mail-based back-up and support [ 22 ], or alternatively, the delivery of printed matter, appointment-reminder telephone calls and mail with educational messages about the disease [ 23 ]. In this respect, there would seem to be agreement on the need to use a combination of strategies to improve adherence, thus surpassing the possible benefits of single strategies implemented one at a time [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%